2004
DOI: 10.1542/peds.113.4.775
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Course, and Prediction of Hyperbilirubinemia in Near-Term and Term Newborns

Abstract: Near-term newborns should not be treated as term newborns in the approach to management of hyperbilirubinemia, because infants of 35 to 37 weeks' gestation had significantly lower birth weights, significantly higher serum total bilirubin levels on days 5 and 7, and were 2.4 times more likely to develop significant hyperbilirubinemia than those of 38 to 42 weeks' gestation in the present study. In near-term newborns of 35 to 37 weeks' (245 to 265 days') gestation, the decision to diagnose and treat significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
135
4
14

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(163 citation statements)
references
References 18 publications
10
135
4
14
Order By: Relevance
“…Thus all new borns should be considered for screening irrespec ve of sex and mode of delivery. This was consistent with observa ons of S Umit et al 12,17 and Frauk Aplay et al 4 Birth weight did not have any bearing on the development of signifi cant jaundice. Mean birth wt.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Thus all new borns should be considered for screening irrespec ve of sex and mode of delivery. This was consistent with observa ons of S Umit et al 12,17 and Frauk Aplay et al 4 Birth weight did not have any bearing on the development of signifi cant jaundice. Mean birth wt.…”
Section: Discussionsupporting
confidence: 91%
“…4 S Umit Sarici et al reported birth weight of 2794±418gm and 2772±157gm in two groups. 17 S Umit et al observed mean birth weight of 3214±828gmgm and 3212± 196 gm in two groups 12 .…”
Section: Discussionmentioning
confidence: 96%
“…The near-term infant is at increased risk for temperature instability, hypoglycemia, respiratory distress, apnea and bradycardia, and clinical jaundice (Wang et al, 2004). The baby's difficulty in coordinating suck/swallow and breathing abilities contributes to problems with feeding; subsequently, poor feeding adds an increased risk of hyperbilirubinemia (Sarici et al, 2004). Near-term infants are 2.4 times more likely than full-term infants to develop significant hyperbilirubinemia (Sarici et al, 2004).…”
Section: Risks Of Inductionmentioning
confidence: 99%
“…The baby's difficulty in coordinating suck/swallow and breathing abilities contributes to problems with feeding; subsequently, poor feeding adds an increased risk of hyperbilirubinemia (Sarici et al, 2004). Near-term infants are 2.4 times more likely than full-term infants to develop significant hyperbilirubinemia (Sarici et al, 2004). Even ''well'' near-term infants who have a normal hospital stay are at increased risk for hospital readmittance, most frequently due to inadequate feeding and to jaundice (Bhutani et al, 2004;Escobar et al, 2005;Wang et al, 2004 Burus-Frank, & Santa-Donato, 2005) is an excellent summary of the problem, the research, and practice implications.…”
Section: Risks Of Inductionmentioning
confidence: 99%
“…2 Significant jaundice is found in 10.5% of term and 25.3% of late preterm infants. 3,4 Therefore each case must be evaluated to detect at risk babies and follow up should be continued even after discharge from hospital as bilirubin level may vary over time and may not peak until 5 th day of life or later to prevent significant morbidity. 2 The gold standard for measurement of billirubin level in newborn is total serum billirubin estimation (TSB).…”
Section: Introductionmentioning
confidence: 99%